2019
DOI: 10.3390/met9121334
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization on Multilayer Morphology During 316L Double-wire CMT+P Deposition Process

Abstract: Cold metal transfer (CMT) has been widely used in metal additive manufacturing for its low heat input, less splashing and high efficiency. Wire feeding speed and travelling speed are important processes that affect morphology in CMT deposition. This study optimized the forming process of 30-layer stainless-steel part deposited by double-wire and double-arc CMT plus pulse (CMT+P) process, and investigated the effect of the ratio of wire feeding speed to travelling speed on deposition morphology. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Pulse can change the current output by accelerating the flow rate of electrons, which makes up for the deficiency of the typical CMT welding process, that is, the small weld depth and only suitable for thin plate welding. It is easy to obtain a welded joint with a relatively large weld depth-to-width ratio [ 23 , 24 , 25 , 26 , 27 ]. In this study, the DP980 dual-phase steel plate with 1.2 mm thickness was welded by the CMT + P welding technology.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse can change the current output by accelerating the flow rate of electrons, which makes up for the deficiency of the typical CMT welding process, that is, the small weld depth and only suitable for thin plate welding. It is easy to obtain a welded joint with a relatively large weld depth-to-width ratio [ 23 , 24 , 25 , 26 , 27 ]. In this study, the DP980 dual-phase steel plate with 1.2 mm thickness was welded by the CMT + P welding technology.…”
Section: Introductionmentioning
confidence: 99%
“…The stress-strain curves measured at the same position of tensile specimens are illustrated in Figure 6, and the average tensile strength and elongation are provided in Table 1. Compared with the sample without auxiliary gas process manufactured by Wu et al [2], both the tensile strength and elongation were increased, which indicated that the auxiliary gas process could improve the performance. In addition, according to the average tensile strength, it could be seen that the auxiliary gas of 30 • had some stirring and cooling effect on the unsolidified molten pool, resulting in a relatively better tensile strength performance.…”
Section: Tensile Propertiesmentioning
confidence: 79%
“…Design-Expert software was used to analyze the evaluation results, and then the regression equation was obtained as follows: R = 94.62−0.021A−3.14B−1.03C + 0.105AB−0.057AC + 0.276BC + 0.0064A 2 −0.291C 2 −0.0035A 2 B + 0.0017A 2 C + 0.0019AC 2 where A indicates the angle between the nozzle and the welding torch, B represents the auxiliary gas flow rate, C expresses the distance from the nozzle to the substrate, and R indicates the comprehensive score of the deposition.…”
Section: Parameters Modeling and Optimal Prediction Of Auxiliary Gas ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization of CMT technology is mainly achieved by applying pulses. Wu et al (2019) used the double-wire CMT + P process to obtain the 316 L stainless steel multilayer, and found that asynchronous arc striking and extinguishing can improve the forming. Increasing the wire feeding and decreasing the welding speed can increase the deposition rate, but it will cause the crystalline grains coarser due to the heat accumulation and reduction in the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%